An offset cancellation technique for SRAM sense amplifier based on relation of the delay and offset. (October 2022) - Zhao, Yue; Wang, Jinkai; Tong, Zhongzhen; Wu, Xiulong; Peng, Chunyu; Lu, Wenjuan; Zhao, Qiang; Lin, Zhiting
Abstract: Sense amplifiers (SA) are facing increasing offset problems and amplifying problems due to mismatch of transistors and variations. This paper presents a structure that cancels the offset which is based on the delay and offset relation. The proposed structure can measure the delay of an SA due to its own offset voltage, and convert it into the length of a correction signal. The correction signal discharges the input of the SA, which reduces the voltage of the input to cancel the offset of the SA. The proposed technique can be applied to both the conventional latch-type SA (CLSA) and the current-latched SA with an NMOS footswitch (CSANF). The schematic simulations based on the 28 nm complementary metal-oxide semiconductor process show that the proposed technique can achieve a more centralized offset distribution than the CLSA and the CSANF. Moreover, the offset voltage of the two types SA can be reduced by 71.42% and 65.95%, respectively.